EXECUTIVE FUNCTION AND EMOTION REGULATION IN PATIENT WITH SCHIZOPHRENIA - Radha,; Dwivedi, Satyadhar (International Journal of Psychosocial Rehabilitation, 2024)
The executive function (EF) is a part of the frontal lobe of the brain. It is a set of capabilities,which permit individuals to implore voluntary control of their behavioral responses. Thesefunctions enable human beings to develop and carry out plans, makeup analogies, obey socialrules, solve problems, adapt to unexpected circumstances, do many tasks simultaneously, andlocate episodes in time and place. On the other hand,Emotion regulation refers to the processesby which a person influences which emotions he has, when he has them, and how he experiencesand expresses them (Gross, 1998).Emotion regulation involves changes in “emotion dynamics”or the latency, rise time, magnitude, duration, and offset of responses in behavioral, experiential,or physiological domains (Thompson, 1991).Objective:To investigate the relationship betweenthe executive function and emotional regulation in patients with schizophrenia.Methods: Presentstudy is the cross-sectional correlation design. The subjects in the study included 40 adultpatients out of which 20 female patients and 20 male patients having a diagnosis ofschizophrenia according to the criteria of ICD10 were selected by purposive sampling. Theinformation was collected by neuropsychological testing and psychological testing. Results: Inthis study, results revealed that cognitive reappraisal is positively correlated with the number ofcategories completed on WCST and word scores on the Stroop color-word test.Conclusion:schizophrenia is a chronic illness, patients with schizophrenia have a lack of theability to regulate their emotions. Emotional dysregulation is present at experiential, processing,and expressing levels, exacerbating distress and social dysfunction experienced. On the otherhand, patients have difficulty carrying plans, makeup analogies, and solve problems